3D Printed Monolithic Device for the Microfluidic Capture, Perfusion, and Analysis of Multicellular Spheroids - Markoski, Alex; Wong, Ian Y.; Borenstein, Jeffrey T. (Frontiers in Medical Technology, 2021)
Microfluidic systems for the analysis of tissue models of cancer and other diseases are rapidly emerging, with an increasing recognition that perfusion is required to recapitulate critical aspects of the in vivo microenvironment. Here we report on the first application of 3D printing for the fabrication of monolithic devices suitable for capturing and imaging tumor spheroids under dynamic perfusion flow. Resolution of the printing process has been refined to a level sufficient to obtain high precision features that enable capture and retention of tumor spheroids in a perfusion flow stream that provides oxygen and nutrient requirements sufficient to sustain viability over several days. Use of 3D printing enables rapid design cycles, based on optimization of computational fluid dynamic analyses, much more rapidly than conventional techniques involving replica molding from photolithographic masters. Ultimately, these prototype design and fabrication approaches may be useful in generating highly multiplexed monolithic arrays capable of supporting rapid and efficient evaluation of therapeutic candidates in the cancer drug discovery process.